Assessment of induced genetic variability through physical mutations in Cenchrus ciliaris L. By Issr markers - López Colomba, Eliana (2015)
Fil: López Colomba, Eliana. Instituto Nacional de Tecnología Agropecuaria. Centro de Investigaciones Agropecuarias; Argentina.